Adjusting the Si Phase and Forming Nanoprecipitation to Improve the Mechanical Properties of Al–Si–Cu–Mg Alloy by Heat Treatment. Issue 5 (8th February 2021) - Hao, Jianfei; Yu, Baoyi; Bian, Jiancong; Liu, Jinmin; Sun, Wanting; Shi, Yuanji; Li, Runxia
Abstract : To adjust the morphology of the Si phase and improve the mechanical properties of Al–Si–Cu–Mg alloy formed by semisolid squeeze casting, the effects of solution time on microstructure evolution and mechanical properties are systematically studied. Results show that spheroidization occurs in the Si phase, and the content of Cu in the matrix increases simultaneously after solution treatment at 525 °C for 1 h. As solution time increases to 8 h, the content of Cu in the matrix increases from 1.15% to 1.41% and the dislocation density decreases. After an aging treatment at 180 °C for 12 h, the β′, θ′, and Q′ phases precipitate. After heat treatment, the alloy strength value shows a "double peak" phenomenon. After a 1 h solution treatment, the tensile strength of the alloy reaches the first peak, which is mainly ascribed to the large dislocation density induced by the semisolid squeeze casting process. When the solution time is 8 h, the tensile strength of the alloy is 323 MPa and the tensile strength reaches the second peak, which is ascribed to the rounding of the Si phase and the strengthening effects of fine precipitates. Abstract : In the early stage of solution treatment, the Cu element quickly dissolves into the matrix. The lath‐shaped β′, short rod‐shaped θ′, and point‐like Q′ phases precipitate after aging treatment. The strength of hypereutectic Al–Si–Cu–Mg alloys formed by semisolid squeeze casting exhibits a "double peak" phenomenon after T6 heat treatment.